Non-destructive assessment, full-scale load-carrying tests and local interventions on two historic timber collar roof trusses - Branco, Jorge M. (2017)
Retrofitting of existing timber roofs may be necessary due to new needs of use or due to the historical significance of the structure. In both cases, a thorough understanding of the existing structure must be available in order to decide the best intervention method. This understanding requires both the assessment of the present state of conservation of the structure, as well as its original and present structural performance. In this paper, two collar trusses belonging to an old building were surveyed and assessed by means of non-destructive methods and evaluated structurally by full-scale load-carrying tests made at the laboratory. The trusses were first tested until failure in their present condition and then tested again after applying two different types of repairs. The interventions consisted on the strengthening of the support regions and local repairs at the failure areas of the rafters using either screwed timber elements or metal plates. The strengthening of the support regions allowed to obtain a higher load level compared to the initial conditions, while the local repair of the timber rafters allowed to partially regain the original load bearing capacity of the trusses compared to results obtained prior to the rafters initial failure.